Penentuan hydrologic soil group untuk perhitungan debit banjir Di Daerah Aliran Sungai Brantas Hulu - Anri Noor Annisa Ramadan; Wanny K Adidarma; Bambang Adi Riyanto; Kamsiyah Windianita (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2017)
Dams are planned and built to be used for water resources activities. Besides the benefits, there were a great danger if the inability of the dam structure to holding the flood is available. The choice of the right method for the magnitude of the plan flood is part of the dam security. Problems that occurred in Indonesia former record data from AWLR is not available. One method of losses flood modeling is NRCS-CN. Moreover, this method can be used for areas without flood hydrograph or reservoir water leveldata, however rainfall record data is available. In CN's determination, Indonesia does not have a HSG (Hydrologic Soil Group) map that needs to be made from another soil map like HWSD. The research was conducted using CN method using land map (HWSD), land use (BAPPEDA). Losses were carried out with HEC-HMS model. The study was conducted in the Upper Brantas basin withSutai Dam outlet. The simulation was done by calibrating the water level. HSG groups obtained from HWSD maps in Upper Brantas basin are A (loamy sand), B (loam), and D (clay). Determination of HSG from HWSD soil map with NRCS-CN loss method and NRCS UH resulted the best calibration of AMC II and ? = 0.2 in March 2007 (RMSE = 0,55) and AMC II and ? = 0.05 December 2007 (RMSE = 0.65).